Natural convection of aluminium oxide-water nanofluid - Afifah, A. N. (Penerbit UTM Press, 2015)
As suspending nanoparticles in fluid-based give tremendous promise in heat transfer application, an understanding on the mechanism of heat transfer is indispensable. The present study dealt with natural convection of nanofluid inside a square cavity heated at the bottom, while the upper part was exposed to the atmosphere. Experimental studies have been performed for various physical conditions, such as volume fractions of nanoparticles varying from 0% to 2.0%, different dispersion techniques of nanoparticles in fluid-based, and heating time from 0 to 35 minutes. In general, dynamic viscosity of nanofluid clearly increased with volume fraction, but decreased with the increasing temperature. It was found that improper dispersion technique resulted in viscous solution. On top of that, transport mechanism of thermophoresis and Brownian diffusion were considered in analysing heat transfer across the cavity.